ANALISIS PENERAPAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI LPKA KELAS I PALEMBANG - M. Afief Rifqi; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
The Child Special Guidance Institution or abbreviated as LPKA is a place for children to serve their criminal period. LPKA itself is a Technical Implementing Unit whose position is under and at the same time responsible to the Director General of Corrections. Transformational leadership is a process in which leaders and their subordinates strive to achieve higher levels of morality and motivation. According to Bass and Avolio (1994), transformational leadership styles that affect employee performance in order to create goals include dimensions/behaviors or better known as 4-I which is then applied to the Palembamg Class I LPKA. preparation of the organization's vision, mission, goals, and program activities. The inspirational motivation component possessed by superiors is not only using one leadership style but always looking at the situations and conditions they face. The intellectual stimulation component is the superior instilling work completion in a deft, timely manner, and the superior also avoids patronizing the employees but invites them to cooperate with each other. The individualized consideration component is the supervisor always follows up on employee needs, always holds workshops or training.